2021
DOI: 10.1007/s12520-021-01365-6
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomy of an excavated striped hyena (Hyaena hyaena) den in Arabia: implications for paleoecology and prehistory

Abstract: Studies of modern carnivore accumulations of bone (i.e., neo-taphonomy) are crucial for interpreting fossil accumulations in the archaeological and paleontological records. Yet, studies in arid regions have been limited in both number and detailed taphonomic data, prohibiting our understanding of carnivore bone-accumulating and -modifying behavior in dry regions. Here, we present a taphonomic analysis of an impressive carnivore-accumulated bone assemblage from the Umm Jirsan lava tube in the Harrat Khaybar reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 88 publications
(138 reference statements)
1
18
0
Order By: Relevance
“…It also suggests a band of moisture in southern Iran that during MIS 5 reached as far northeast as the Jazmurian playa, as we tentatively suggest in the previous section. It also captures the minimum latitudinal extent of MIS 5 monsoonal moisture indicated by field investigations in adjacent regions including Arabia [ 35 , 103 ].…”
Section: Resultsmentioning
confidence: 93%
“…It also suggests a band of moisture in southern Iran that during MIS 5 reached as far northeast as the Jazmurian playa, as we tentatively suggest in the previous section. It also captures the minimum latitudinal extent of MIS 5 monsoonal moisture indicated by field investigations in adjacent regions including Arabia [ 35 , 103 ].…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, the incorporation of gazelle may be an indicator of climatic conditions with a tendency towards aridity. This is further suggested by the presence of the coprolites, most probably associated with the striped hyena, which lives predominantly in arid/semi-arid environments and in savannah areas, with their remains attested to the southeast on the Harrat Khaybar [40]. The low frequency of gazelle remains may indicate a mixed economy based on herding and hunting [25,76,77,80,84,85].…”
Section: Plos Onementioning
confidence: 95%
“…The spherical shape of the pellets, with tip and dimple on the underside is comparable with the segmented faeces of hyaenids, formed by around 10 droppings each [38]. Their size around 15-25 mm suggests a possible attribution to the striped hyena (Hyaena hyaena; [39]), which was distributed in the area [13,40]. Their pale colour, a consequence of feeding habits, which includes consuming bone, is consistent with this attribution and suggests an adult [39].…”
Section: Plos Onementioning
confidence: 97%
“…The importance of cave bears and hyenas in the formation of the examined cave sites is not surprising, since both animals are established depositional agents in Paleolithic cave sites. Hyenas typically accumulate large amounts of animal and human bones, as well as organicrich feces, in their dens (e.g., Horwitz & Smith, 1988;Kerbis-Peterhans & Horwitz, 1992;Stewart et al, 2021). In many Pleistocene caves with a mixed human-hyena occupation, multi-disciplinary studies have demonstrated that hyena activity is one of the main processes of site formation while anthropogenic influence in the site assemblage might be limited (Discamps et al, 2012;Mangano, 2011 and references therein;Maroto et al, 2012;Samper Carro & Martínez-Moreno, 2014;Crezzini et al, 2016;Sanz & Daura, 2018;Villa et al, 2010;Sala et al, 2021).…”
Section: Interaction Between Animals and Humans In Caves And Rockshel...mentioning
confidence: 99%